Characteristic of volatile flavor compounds in ‘Fengtangli’ plum (Prunus salicina Lindl.) were explored based on GC×GC-TOF MS - Hu, Xianfeng; Li, Deyan; Ding, Yi; Zhang, Yubo; Ren, Chunguang (Frontiers in Nutrition, 2025)
IntroductionThe ‘Fengtangli’ plum (Prunus salicina Lindl.) is favoured by consumers for its characteristic flavor. The purpose of this study was to explore the characteristics of volatile flavor compounds in ‘Fengtangli’ plum.MethodsThe flavor compounds of both ‘Fengtangli’ and ‘Siyueli’ plums were analyzed using comprehensive two-dimensional gas chromatography time-of-flight mass spectrometry (GC×GC-TOF MS).ResultsThe results revealed the presence of 495 volatile flavor compounds in ‘Fengtangli’ plum and 466 in ‘Siyueli’ plum. The relative concentrations of hydrocarbons, alcohols, ketones, and esters in ‘Fengtangli’ plum were significantly elevated compared to those detected in ‘Siyueli’ plum. Moreover, the sensorial attributes of sweetness, citrus, herbal, floral, and fruity notes were more prominent in ‘Fengtangli’ plum relative to those of ‘Siyueli’ plum. Through the integration of differential metabolite analysis and relative odor activity assessment, it is hypothesized that furan-2-pentyl; (E)-2-octenal; and 1-octen-3-one may represent the characteristic of volatile flavor compounds in ‘Fengtangli’ plum.DiscussionThe research results may provide a theoretical reference for the development and application of ‘Fengtangli’ plum and the study of the synthesis mechanism of characteristic flavor compounds.